The reasons for the low conceptual comprehension of the fourth-grade students in science from the point of view of teachers and supervisors - Al-Fifi, Kathiyah Mohammed Salem (Journal of Curriculum and Teaching Methodology, 2022)
The research aimed to identify the reasons for the low conceptual comprehension of the fourth grade students in science from the point of view of teachers and supervisors, in the Education Departments of Sabya Governorate and Jazan Region. From (118) female teachers, and (16) supervisors were randomly selected from the research community, which amounted to (322) female teachers of the fourth grade of primary school, and (23) female science supervisors for the primary stage in the Education Departments of Sabya Governorate and Jazan Region. It was concluded that the approval of the research sample on the reasons for the low conceptual comprehension of the fourth grade students in science from the point of view of teachers and supervisors came to a high degree, and the results showed that there were statistically significant differences at the significance level (0.01) between the estimates of both science teachers and supervisors. In the Education Departments of Sabya Governorate and Jazan Region, about the reasons for the low conceptual comprehension of the fourth graders in favor of the female supervisors. Suspicion for science teachers and interest in teacher preparation programs to be trained in the basics of teaching and planning, familiarity with the various teaching methods, and rehabilitating them with all modern methods of education and various strategies, production and design of educational aids from the local environment, and how to apply them to the success of the conceptual assimilation process in teaching the process of conceptual assimilation. curricula.